PERBANDINGANÃÂ MODELÃÂ PEMBELAJARANÃÂ KONVENSIONALÃÂ DANÃÂ KOOPERATIFÃÂ TIPEÃÂ JIGSAWÃÂ TERHADAPÃÂ HASILÃÂ BELAJARÃÂ KOMPETENSIÃÂ PERBAIKANÃÂ SISTEMÃÂ PENGAPIANÃÂ ÃÂ ÃÂ - UtomoÃƒÂ‚Ã‚Â , Prasetyo; Winarno, -; SuwahyoÃƒÂ‚Ã‚Â , - (Jurnal Pendidikan Teknik Mesin, 2008)
TujuanÃÂ dariÃÂ penelitianÃÂ iniÃÂ adalahÃÂ untukÃÂ membandingkanÃÂ hasilÃÂ belajarÃÂ kompetensiÃÂ perbaikanÃÂ sistemÃÂ pengapianÃÂ  yangÃÂ  pembelajarannyaÃÂ  disampaikanÃÂ  denganÃÂ menggunakanÃÂ modelÃÂ  pembelajaranÃÂ  konvensionalÃÂ  danÃÂ modelÃÂ kooperatifÃÂ  tipeÃÂ  Jigsaw.ÃÂ  PopulasiÃÂ  dalamÃÂ  penelitianÃÂ  iniÃÂ  adalahÃÂ  108ÃÂ  orangÃÂ  siswaÃÂ  kelasÃÂ  XÃÂ  TeknikÃÂ MekanikÃÂ  OtomotifÃÂ (TMO)ÃÂ SMKÃÂ NegeriÃÂ 4ÃÂ SemarangÃÂ tahunÃÂ AjaranÃÂ 2008/2009ÃÂ yangÃÂ terdiriÃÂ atasÃÂ 36ÃÂ siswaÃÂ kelasÃÂ XÃÂ TMOÃÂ 1,ÃÂ 36ÃÂ siswaÃÂ kelasÃÂ XÃÂ TMOÃÂ 2,ÃÂ danÃÂ 36ÃÂ siswaÃÂ kelasÃÂ XÃÂ TMOÃÂ 3.ÃÂ PenelitianÃÂ iniÃÂ adalahÃÂ penelitianÃÂ eksperimenÃÂ denganÃÂ desainÃÂ ControlÃÂ groupÃÂ preÃÂtestÃÂpostÃÂtest.ÃÂ HasilÃÂ belajarÃÂ pembelajaranÃÂ menggunakanÃÂ modelÃÂ pembelajaranÃÂ kooperatifÃÂ tipeÃÂ jigsawÃÂ mengalamiÃÂ peÃ¢â¬ÂningkatanÃÂ dariÃÂ perolehanÃÂ rataÃ¢â¬ÂrataÃÂ awalÃÂ sebesarÃÂ 68,49ÃÂ menjadiÃÂ 83,17ÃÂ setelahÃÂ pembelajaran.ÃÂ ÃÂ PeningkatanÃÂ iniÃÂ menÃ¢â¬ÂcapaiÃÂ 56,11%.ÃÂ PeningkatanÃÂ hasilÃÂ belajarÃÂ kelompokÃÂ kontrolÃÂ hanyaÃÂ mencapaiÃÂ 24,73%;ÃÂ yaituÃÂ dariÃÂ kemampuanÃÂ awalÃÂ sebesarÃÂ 68,57ÃÂ menjadiÃÂ 78,81.ÃÂ HalÃÂ iniÃÂ menunjukkanÃÂ bahwaÃÂ hasilÃÂ belajarÃÂ yangÃÂ pembelajarannyaÃÂ menggunakanÃÂ modelÃÂ pembelajaranÃÂ kooperatifÃÂ tipeÃÂ jigsawÃÂ lebihÃÂ baikÃÂ dibandinganÃÂ denganÃÂ modelÃÂ konvensional. ÃÂ  KataÃÂ Kunci:ÃÂ KooperatifÃÂ tipeÃÂ Jigsaw,ÃÂ konvensionalÃÂ danÃÂ hasilÃÂ belajar.TheÃÂ objectiveÃÂ ofÃÂ thisÃÂ researchÃÂ isÃÂ toÃÂ compareÃÂ betweenÃÂ theÃÂ studyÃÂ  resultÃÂ withÃÂ  repairÃÂ  ignitionÃÂ systemÃÂ competenceÃÂ  inÃÂ whichÃÂ  theÃÂ  learningÃÂ  isÃÂ presentedÃÂ usingÃÂ conventionalÃÂ andÃÂ  jigsawÃÂ cooperativeÃÂ  learningÃÂ model.ÃÂ TheÃÂ populationÃÂ ofÃÂ  theÃÂ researchÃÂ wasÃÂ 108ÃÂ studentsÃÂ ofÃÂ tenthÃÂ gradeÃÂ inÃÂ AutomotiveÃÂ MechanicalÃÂ EngineeringÃÂ (TMO)ÃÂ atÃÂ SMKÃÂ NegeriÃÂ 4ÃÂ SemarangÃÂ yearÃÂ 2008/2009ÃÂ  thatÃÂ couldÃÂ beÃÂ dividedÃÂ  intoÃÂ 36ÃÂ  tenthÃÂ gradersÃÂ ofÃÂ TMOÃÂ 1,ÃÂ 36ÃÂ tenthÃÂ gradersÃÂ ofÃÂ TMOÃÂ 2,ÃÂ andÃÂ 36ÃÂ tenthÃÂ gradersÃÂ ofÃÂ TMOÃÂ 3.ÃÂ ThisÃÂ researchÃÂ isÃÂ experimentalÃÂ oneÃÂ withÃÂ ControlÃÂ GroupÃÂ PreÃÂTestÃÂPostÃÂTestÃÂ design.ÃÂ TheÃÂ studentÃÂ reÃ¢â¬ÂsultÃÂ  usingÃÂ  cooperativeÃÂ  learningÃÂ modelÃÂ  jigsawÃÂ  typeÃÂ  getsÃÂ  improvementÃÂ  fromÃÂ  firstÃÂ  averageÃÂ  gainingÃÂ  aboutÃÂ  68,49ÃÂ  toÃÂ 83,17ÃÂ  afterÃÂ  learning.ÃÂ  ThisÃÂ  improvementÃÂ  percentageÃÂ  achievesÃÂ  56,11%.ÃÂ Meanwhile,ÃÂ  theÃÂ  studyÃÂ  resultÃÂ improvementÃÂ percentageÃÂ inÃÂ controlledÃ¢â¬ÂgroupÃÂ onlyÃÂ achievesÃÂ 24,73%.ÃÂ ItÃÂ isÃÂ fromÃÂ firstÃÂ abilityÃÂ aboutÃÂ 68,57ÃÂ toÃÂ 78,81.ÃÂ ItÃÂ showsÃÂ thatÃÂ theÃÂ studyÃÂ resultÃÂ usingÃÂ jigsawÃÂ cooperativeÃÂ learningÃÂ modelÃÂ isÃÂ betterÃÂ thatÃÂ theÃÂ conventionalÃÂ one. ÃÂ  Keywords:ÃÂ jigsawÃÂ cooperativeÃÂ model,ÃÂ conventionalÃÂ andÃÂ studyÃÂ result